The IVP Bible background commentary : New Testament - Keener, Craig S., 1960-; Keener Craig S.; InterVarsity Press (Downers Grove, IL : InterVarsity Press, 2014)
"To understand and apply the Bible well, you need two crucial sources of information. One is the Bible itself. The other is an understanding of the cultural background of the passage you're reading. Only with this background can you grasp the author's original concerns and purposes. This unique commentary provides, in verse-by-verse format, the crucial cultural background you need for responsible--and richer--Bible study. This revised edition of the standard reference work in its field has been expanded throughout to now provide even more up-to-date information by one of the leading New Testament scholars on Jewish, Greek, and Roman culture ... Included are a glossary of cultural terms and important historical figures, maps and charts, up-to-date bibliographies, and introductory essays about cultural background information for each book of the New Testament. This must-have resource is just what's needed for: pastors in sermon preparation; Sunday-school and other church teachers as they build lessons; missionaries concerned not to import their own cultural biases into the Bible; college and seminary students in classroom assignments; and everyday Bible readers seeking to deepen and enhance their study of Scripture."--Dust jacket.
Preface and acknowledgments -- List of abbreviations -- How to use this commentary -- The need for a cultural-historical commentary -- Gospels -- Matthew -- Mark -- Luke -- John -- Acts -- New Testament letters -- Romans -- 1 Corinthians -- 2 Corinthians -- Galatians -- Ephesians -- Philippians -- Colossians -- 1 Thessalonians -- 2 Thessalonians -- 1 Timothy -- 2 Timothy -- Titus -- Philemon -- Hebrews -- James -- 1 Peter -- 2 Peter -- 1 John -- 2 John -- 3 John -- Jude -- Revelation -- Glossary -- Maps and charts -- Old Testament scripture index.
Includes bibliographical references.
Keywords: Bible. -- Commentaries